DESVENDANDO IMAGINÁRIOS: gênero e sexualidade na perceção de famílias de alunos e alunas da Educação Infantil da rede pública municipal de ensino de Cascavel-PR - Santos, Mayara dos (2024)
This research investigates the imaginaries of gender and sexuality in the perceptions of representatives of families of students of public Early Childhood Education in Cascavel, PR, aiming to understand how these issues are discussed, assimilated and transmitted in the family context. It is assumed that knowledge about gender and sexuality is socially constructed since childhood, being transmitted through diverse interactions. In this process, different imaginaries are assimilated and incorporated, with school and family playing fundamental roles. The research adopts a qualitative and exploratory approach, combining bibliographic analysis with field research based on interviews. The theoretical framework is based on the formist phenomenology of Michel Maffesoli (1998) and on the reflections of Jean François Lyotard (1988; 1994) on postmodernity and the end of metanarratives. In the field of gender and sexuality studies, the contributions of Guacira Lopes Louro (2000; 2008; 2010), Judith Butler (2017) and Michel Foucault (1988) stand out, who discuss the concepts of gender, sexuality and body as social constructions in constant transformation. The approach to imaginaries is based on the works of Gilbert Durand (1998; 2012) and Maffesoli (2001; 2010), who analyze the symbolic and collective dimensions of these imaginaries. The results indicate that the representatives of the families interviewed have a predominantly binary view of gender and a heteronormative view of sexuality, believing that education on these topics should occur exclusively within the family. This perspective reveals the need for pedagogical work that is sensitive and welcoming, capable of dialoguing with these different conceptions, without losing sight of the importance of expanding understandings about gender and sexuality. The conclusions highlight the role of the school as a potential space for change. By strengthening the dialogue with families, the school can propose educational practices that embrace diversity and respect the different ways of existing.